Epistatic effect of TLR3 and cGAS-STING-IKKε-TBK1-IFN signaling variants on colorectal cancer risk - Catalano, Calogerina; da Silva Filho, Miguel Inacio; Frank, Christoph; Lu, Shun; Jiraskova, Katerina; Vymetalkova, Veronika; Levy, Miroslav; Liska, Vaclav; Vycital, Ondrej; Naccarati, Alessio; Vodickova, Ludmila; Hemminki, Kari; et al. (Cancer medicine, 2020)
OBJECTIVE: The TLR3/cGAS-STING-IFN signaling has recently been reported to be disturbed in colorectal cancer due to deregulated expression of the genes involved. Our study aimed to investigate the influence of potential regulatory variants in these genes on the risk of sporadic colorectal cancer (CRC) in a Czech cohort of 1424 CRC patients and 1114 healthy controls. METHODS: The variants in the TLR3, CGAS, TMEM173, IKBKE, and TBK1 genes were selected using various online bioinformatic tools, such as UCSC browser, HaploReg, Regulome DB, Gtex Portal, SIFT, PolyPhen2, and miRNA prediction tools. RESULTS: Logistic regression analysis adjusted for age and sex detected a nominal association between CRC risk and three variants, CGAS rs72960018 (OR: 1.68, 95% CI: 1.11-2.53, P-value = .01), CGAS rs9352000 (OR: 2.02, 95% CI: 1.07-3.84, P-value = .03) and TMEM173 rs13153461 (OR: 1.53, 95% CI: 1.03-2.27, P-value = .03). Their cumulative effect revealed a threefold increased CRC risk in carriers of 5-6 risk alleles compared to those with 0-2 risk alleles. Epistatic interactions between these genes and the previously genotyped IFNAR1, IFNAR2, IFNA, IFNB, IFNK, IFNW, IRF3, and IRF7 genes, were computed to test their effect on CRC risk. Overall, we obtained nine pair-wise interactions within and between the CGAS, TMEM173, IKBKE, and TBK1 genes. Two of them remained statistically significant after Bonferroni correction. Additional 52 interactions were observed when IFN variants were added to the analysis. CONCLUSIONS: Our data suggest that epistatic interactions and a high number of risk alleles may play an important role in CRC carcinogenesis, offering novel biological understanding for the CRC management.
Keywords: Interferons; senioři; I-kappa B Kinase; toll-like receptor 3; membránové proteiny; signální transdukce; rektum; senioři nad 80 let; jednonukleotidový polymorfismus; Membrane Proteins; Toll-Like Receptor 3; Male; kolorektální nádory; Healthy Volunteers; kinasa I-kappa B; výpočetní biologie; regulace genové exprese u nádorů; mladiství; Cohort Studies; genetická epistáze; genotypizační techniky; Middle Aged; protein-serin-threoninkinasy; mužské pohlaví; Colorectal Neoplasms; Signal Transduction; polygenic-risk-score; studie případů a kontrol; Carcinogenesis; Adult; mladý dospělý; CRC; kohortové studie; Genotyping Techniques; Colonoscopy; interferony; Colon; Aged, 80 and over; Protein Serine-Threonine Kinases; Polymorphism, Single Nucleotide; Young Adult; Nucleotidyltransferases; risk; ženské pohlaví; Epistasis, Genetic; Gene Expression Regulation, Neoplastic; Humans; kolon; lidé středního věku; nukleotidyltransferasy; dospělí; Computational Biology; Female; Aged; karcinogeneze; Rectum; Adolescent; interaction; lidé; Case-Control Studies; kolonoskopie; zdraví dobrovolníci pro lékařské studie